1975
DOI: 10.2337/diab.24.10.865
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of Glucose Metabolism and of the Citrate Cleavage Pathway in Adipose Tissue of Normal and Diabetic Subjects

Abstract: Enzyme activities operative in glucose degradation and citrate cleavage pathway were studied in the adipose tissue of twenty-four patients with adult-onset diabetes and normal body weight, aged 59+/-9 years, and twenty-four matched controls. In normal tissue, type II (heat-inactivated) hexokinase moderately predominated over type I (heat-resistant). 6-Phosphofructokinase had an extremely low activity, which was by far the lowest among the ten glycolytic enzyme activities investigated, and which therefore might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Two additional NADPH forming metabolic cycles were known to occur [22]. One was the hexose monophosphate pathway (HMP), which consisted of the action of G6PDH; the other was the citrate cleavage pathway, which consisted of the sequential action of ACL and ME.…”
Section: Resultsmentioning
confidence: 99%
“…Two additional NADPH forming metabolic cycles were known to occur [22]. One was the hexose monophosphate pathway (HMP), which consisted of the action of G6PDH; the other was the citrate cleavage pathway, which consisted of the sequential action of ACL and ME.…”
Section: Resultsmentioning
confidence: 99%
“…Its activity was found to be significantly lower in adipose tissue of fat compared to lean mice [49]. Belfiore et al [50] also observed a reduction in NADPH-forming enzymes, including malate dehydrogenase, in adipose tissue of diabetic subjects, which suggested depressed lipogenesis. Moreover, downregulation of malate dehydrogenase in BAT is in agreement with the findings of a previous study, where we observed a 3-fold lower expression of this enzyme in BAT of genetically obese Lep ob / Lep ob vs. lean mice [51].…”
Section: Bat Fat Markersmentioning
confidence: 97%
“…The increase in HX activity in diabetic platelets indicates that, unlike in the liver and adipose tissue, the expression of the enzyme in these cells is independent of insulin (26). The lack of significant correlation between HX activity and fructosamine or HbA 1c concentrations in diabetic individuals suggests that prolonged hyperglycaemia may not be a predominant factor affecting enzyme expression (Tables 1, 4, 7).…”
Section: A Very Low Level Of Contamina-mentioning
confidence: 99%